The tone in the auditor's report and the audit fee with emphasis on the moderating role of the requirements of Auditing Standard No. 700 - Masoumeh Shahsavari; Mohammad Reza Abbaszadeh; Hamze hesari (مطالعات تجربی حسابداری مالی, 2023)
In the present study, the relationship between the qualitative information of the auditor's report and the quality of accounting has been discussed. In particular, the relationship between the tone of the auditor's report and the audit fee (audit quality criterion based on the input of the audit process) has been examined with respect to the concepts of risk, client business risk, and litigation risk. To test the research hypotheses, 360-year-firms data of Iranian Stock Exchange were used during a period of 6-years, three years before and three years after the revision of Auditing Standard No. 700. Textual data were analyzed using Maxqda10 text analysis software and after quantification along with other quantitative data were analyzed using multivariate linear regression in Ives software and SPSS Eviews 9. The results indicate a weak inverse relationship between the optimistic tone and the audit fee variable. In addition, the findings showed that the acceptance of the requirements of Auditing Standard No. 700 does not make significant changes in the relationship between the tone of the auditor's report and the remuneration compared to the period before the review. In general, the results of the research indicate evidence of the predominance of the signaling effect (albeit poorly) in the sample.